Inter-hemispheric asymmetry of nigrostriatal dopaminergic lesion: a possible compensatory mechanism in Parkinson’s disease - Blesa, Javier; Juri, Carlos; García-Cabezas, Miguel Ángel; Adánez, Rebeca; Sánchez-González, Miguel Ángel; Cavada, Carmen; Obeso, José A. (Frontiers in Systems Neuroscience, 2011)
The onset of Parkinson's disease (PD) is characterized by focal motor features in one body part, which are usually correlated with greater dopaminergic depletion in the contralateral posterior putamen. The role of dopamine (DA) hemispheric differences in the onset and progression of motor symptoms of PD, however, remains undefined. Previous studies have demonstrated that unilateral manipulations of one nigrostriatal system affect contralateral DA turnover, indicating a functional and compensatory interdependence of the two nigrostriatal systems. In preliminary data obtained by our group from asymmetric PD patients, a higher asymmetry index as measured by 18F-DOPA PET was associated with a higher threshold (i.e. greater dopaminergic loss) for the onset of motor symptoms in the less-affected side. To further elucidate the underlying basis for this, we carried out a complementary study in monkeys using PET to assess and correlate the degree of dopaminergic striatal depletion with motor activity. Control and MPTP-intoxicated monkeys with symmetrical lesions were characterized behaviorally and with 18F-DOPA PET. In parallel, an acute lesion was inflicted in the nigrostriatal projection unilaterally in one monkey, generating a 30% dopaminergic depletion in the ipsilateral striatum, which was not associated with any noticeable parkinsonian feature or deficit. The monkey remained asymptomatic for several months. Subsequently, this monkey received systemic MPTP, following which motor behavior and PET were repeatedly evaluated during progression of parkinsonian signs. The brains of all monkeys were processed using immunohistochemical methods. Our results suggest that the onset of motor signs is related to and influenced by the dopaminergic status of the less-affected, contralateral striatum. Although this work is still preliminary, the study agrees with our general hypothesis of hemispheric interdependence in the compensation of striatal DA deficit in PD.